Regulation of the functions of the supervisor of Higher Education in Puebla, Mexico - Cházaro Arellano, Eva Hortensia (Avances en Supervisión Educativa, 2009)
Regulatory functions of the Supervisor of Higher Education in Puebla, Mexico. The Mexican educational system is regulated by law and standards since the Constitution of the Mexican United States came in force. Within the educational system there are different areas at the nation level as well as at state or city levels which are also ruled by the Constitution and other laws. In the case of the State of Puebla, a public officer -known as Supervisor of Higher Education- has been created, whose functions and duties need regulation urgently. With an origin in the laws in force and from an administrative and epistemological point of view, this article sets up the basis for a draft document in order to regulate the functions of Supervisors.